2021
DOI: 10.3389/fendo.2021.761834
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Butyrate for Treatment of Type 2 Diabetes

Abstract: Metagenomics studies have shown that type 2 diabetes (T2D) is associated with an altered gut microbiota. Whereas different microbiota patterns have been observed in independent human cohorts, reduction of butyrate-producing bacteria has consistently been found in individuals with T2D, as well as in those with prediabetes. Butyrate is produced in the large intestine by microbial fermentations, particularly of dietary fiber, and serves as primary fuel for colonocytes. It also acts as histone deacetylase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 113 publications
4
35
0
Order By: Relevance
“…38 As for Eubacterium_xylanophilum_group, it has been shown to be able to produce butyrate, a short-chain fatty acid able to increase insulin sensitivity. 39,40 Another increased bacterium was Alloprevotella, and it has been reported that Alloprevotella is also a short-chain fatty-acid producer. 41,42 The liver breaks down toxic substances and prevents bacterial metabolites from entering circulation in the body.…”
Section: Food and Function Papermentioning
confidence: 99%
“…38 As for Eubacterium_xylanophilum_group, it has been shown to be able to produce butyrate, a short-chain fatty acid able to increase insulin sensitivity. 39,40 Another increased bacterium was Alloprevotella, and it has been reported that Alloprevotella is also a short-chain fatty-acid producer. 41,42 The liver breaks down toxic substances and prevents bacterial metabolites from entering circulation in the body.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The GM serves as a crucial auxiliary in nutrition acquisition, maintaining gut homeostasis, and immune programming and playing an important role in host health and disease. 31 During pregnancy, the GM affects maternal and fetal health. 3,32 However, GM modulation of maternal adaptations to pregnancy is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our data suggest that while the shift toward greater kynurenine levels may affect gestational glucose homeostasis, it may have contributions from a reduced AHR axis. Also, butyrate levels associate with and affect insulin sensitivity 31 and may activate the AHR pathway and transcription of AHR-dependent genes in intestine epithelial cells. 30 In our data, a decline in butyrate levels support a disturbed intestinal ecosystem at G15 and may represent another factor affecting pregnancy IR.…”
Section: Discussionmentioning
confidence: 99%
“…(23). Recent research studies have shown that the Clostridia strains secreting butyrate were found in fewer numbers in the intestine of patients with type 2 diabetes mellitus, whereas non-butyrate-producing Clostridiales were found in a higher number of studies that showed that both insulin sensitivity and levels of butyrate-producing intestinal microbiota were markedly increased after microbiota transplantation (24). FMT has recently been shown to be helpful for regulating blood glucose and blood pressure in type 2 diabetic patients when supplemented with a particular diet over the course of a 3-month investigation.…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…( 23 ). Recent research studies have shown that the Clostridia strains secreting butyrate were found in fewer numbers in the intestine of patients with type 2 diabetes mellitus, whereas non-butyrate-producing Clostridiales were found in a higher number of studies that showed that both insulin sensitivity and levels of butyrate-producing intestinal microbiota were markedly increased after microbiota transplantation ( 24 ).…”
Section: Fmt For Extraintestinal Disordersmentioning
confidence: 99%